Profiling at the Canadian border: an economist's viewpoint - Don J. DeVoretz (Institute for the Study of Labor (IZA), 2006)
Scrutiny at the Canadian border to heighten security and simultaneously reduce type one (false positives) and type two (false negatives) errors involves a substantial use of resources as well as imposing opportunities costs in terms of time and trade diversion. One maligned strategy to minimize these costs at the border has been group or racial profiling. This essay develops a pedigree system for Canadian border security which simultaneously reduces both type I and II errors while avoiding racial or group profiling.
urn:nbn:de:101:1-2008042946
Keywords: 330